Artificial Intelligence (Ai) Implementation in Corporate Sustainability Communication - Ni Made Ugura Ditaning Wulandari; Siti Suroya; Nur Ashilah Sulthanah Haq (Institut Nalanda, 2026)
The convergence of artificial intelligence and sustainability demands has transformed corporate communication practices. This study examines how corporations implement AI technologies in sustainability communication strategies and analyzes implications for stakeholder engagement, corporate legitimacy, and narrative authenticity. Employing a qualitative analytical descriptive approach, the research draws upon corporate sustainability reports, industry analyses, and academic literature to investigate technological applications and communicative consequences of AI deployment. The findings reveal that corporations utilize AI across four functional domains: data collection and processing, content generation and reporting, stakeholder monitoring and engagement, and verification support. These implementations offer efficiency gains of 40 to 60 percent in reporting preparation and enhanced consistency in sustainability messaging. However, the analysis identifies tensions between AI enabled efficiency and authenticity concerns, as technologies facilitating transparent disclosure also enable sophisticated greenwashing. Drawing upon legitimacy theory and stakeholder theory, this study argues that AI implementation represents a double edged phenomenon requiring careful governance to realize benefits while mitigating risks to stakeholder trust.